UNIVERSITY GOVERNANCE IN THE CONDITION OF AUTHORITY IN VIETNAM TODAY - Tran Mai Uoc; Vu Thi Thu Huyen; Tran Thi Hoa (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In the current context, under the impact of globalization and the influence of the industrial revolution 4.0, higher education in Vietnam is facing many challenges. With the Law amending and supplementing several articles of the Higher Education Law effective from July 1, 2019, to present (2021), it has helped to complete the legal framework for the renovation of the management of educational institutions university, including content related to autonomy. Autonomy is a necessary condition for the implementation of advanced university administration methods to improve and improve the training quality of higher education institutions in the current period. From the philosophical approach, educational philosophy, and literary studies, through the study and analysis of Vietnamese state legal documents and other relevant documents, this article focuses on studying public university governance study in the conditions of autonomy in Vietnam today. The study shows the basic advantages, disadvantages and challenges through the practical implementation of school governance for (public) higher education institutions in the autonomous condition in Vietnam. The solutions that the article mentions and analyzes to improve university governance in the current state of autonomy are also valuable and make certain contributions to the practice in Vietnam today.